Acute effect of static and dynamic stretching on hip dynamic range of motion during instep kicking in professional soccer players - Amiri-Khorasani, M.; Abu Osman, N. A.; Yusof, A. (The Journal of Strength and Conditioning Research, 2011)
The purpose of this study was to examine the effects of static and dynamic stretching within a pre-exercise warm-up on hip dynamic range of motion (DROM) during instep kicking in professional soccer players. The kicking motions of dominant legs were captured from 18 professional adult male soccer players (height: 180.38 ± 7.34 cm; mass: 69.77 ± 9.73 kg; age: 19.22 ± 1.83 years) using 4 3-dimensional digital video cameras at 50 Hz. Hip DROM at backward, forward, and follow-through phases (instep kick phases) after different warm-up protocols consisting of static, dynamic, and no-stretching on 3 nonconsecutive test days were captured for analysis. During the backswing phase, there was no difference in DROM after the dynamic stretching compared with the static stretching relative to the no-stretching method. There was a significant difference in DROM after the dynamic stretching compared with the static stretching relative to the no-stretching method during (a) the forward phase with p < 0.03, (b) the follow-through phase with p < 0.01, and (c) all phases with p < 0.01. We concluded that professional soccer players can perform a higher DROM of the hip joint during the instep kick after dynamic stretching incorporated in warm-ups, hence increasing the chances of scoring and injury prevention during soccer games.